Sunday

April 20, 2014

April 20, 2014

Posted by **sandra** on Friday, April 27, 2012 at 5:43pm.

a) f(x) = -2(x-1)(x+4)(x+1)(x-3) b) f(x) = (x+2)(x+1)(x+4)

c) f(x) = x(x-6)

2) For each function in question 1. state the degree of the polynomial and identify the type of function

- Math-Funtions -
**Henry**, Sunday, April 29, 2012 at 7:16pm1a. F(x) = -2(x^2-1)(x+4)(x-3).

F(x) = -2(x^2-1)(x^2-3x+4x-12).

F(x) = -2(x^2-1)(x^2+x-12).

F(x) = (-2x^2+2)(x^2+x-12).

F(x) = -2x^4-2x^3+24x^2.

b. F(x) = (x+2)(x+1)(x+4).

F(x) = (x^2+x+2x+2)(x+4).

F(x) = x^3+4x^2+x^2+4x+2x^2+8x+2x+8.

F(x) = x^3+7x^2+14x+8.

c. F(x) = x(x-6).

F(x) = x^2-6x.

2a. 4th degree.

b. 3rd degree.

c. 2nd degree.

**Related Questions**

Math---helpppp - 1)Expand and simplify. Express each equation in standard form. ...

Math-Functions - 1)Expand and simplify. Express each equation in standard form. ...

math/Check! - a. An ellipse is formed by stretching the graph of x^2+ y^2=1 ...

someone please chek my math! - a. An ellipse is formed by stretching the graph ...

Math - Express the following equation 6x-8y=8(x-9)+12 in: 1. Slope intercept ...

MATH/ Check? - Correct. what is pi The definition or the number? The number is 3...

Please check answers) - Perform the indicated operations and simplify the result...

Math 111 - Solve the equation by the square root property. If possible, simplify...

Calculus - Complete the square to write the equation x^2 + y^2 - 6x - 2y + 4 = 0...

math - How do I put an equation into standard form, Ax+Bx=C? I have the given ...